ANALYZING PROJECT BASED LEARNING EFFECTIVENESS AT PLJ DEPOK CAMPUS - Aidil Firdan Janwar; Linda Rosmawati; Adel Lyra Annisa (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The development of vocational education requires the implementation of learning models that can improve students’ competencies actively and in line with the needs of the workforce. One model that is widely used is Project Based Learning (PJBL) because it places students at the center of learning through project completion. This study aims to analyze the effectiveness of Project Based Learning implementation among students of Politeknik LP3I Jakarta Depok Campus. This research used a descriptive quantitative approach with a frequency table method. The data were collected through questionnaires distributed to 81 students who participated in project-based learning in the even semester of the 2025/2026 academic year and were analyzed using a Likert scale. The results showed that the implementation of Project Based Learning obtained an average score of 3.99, which is classified as good. These findings indicate that Project Based Learning is effective in improving the quality of student learning, especially in communication, collaboration, critical thinking, creativity, and project completion. However, several aspects still need to be improved through more optimal guidance during the learning process. Therefore, Project Based Learning can be considered an effective learning model to support the achievement of student competencies in vocational education.